แนวทางการดำเนินงานการจัดการเรียนการสอนรายวิชาเพิ่มเติมหน้าที่ พลเมืองในระดับมัธยมศึกษาตอนต้นของโรงเรียนสังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - จันทัน, พิมพ์ตะวัน; อิศรางกูร ณ อยุธยา, วลัย (An Online Journal of Education, 2018)
The objectives of the research were to study the state and problems of the operation of instructional management of additional civics courses in the lower secondary schools in the aspects of the preparation of teachers, instructional activity organization, instructional material /learning sources and evaluation; to study the desirable characteristics of students developed from the civics courses ; and to purpose guidelines for problem solutions of instructional activity organization. The sample were consisted of teacher-head of social studies subject area, teachers responsible for the civics courses and lower secondary school students totally 1,731 which were selected by multistage random sampling. The questionnaire forms were the research instruments. The research results were as follow: 1) Teachers prepared their teaching by studying the civics course teaching manuals and books related to civics content ;sorting material already had in school stocks. The civics courses were constructed as the additional courses and instructional activities focused on group-working and awareness development , fieldtrips were organized as part of extra curriculum activities. Work sheets ,videos ,textbooks/extra readings were mostly used by teachers. Teachers were main evaluators and students were self-evaluators with an emphasis on students’ behavior by working behavior observation forms. The teachers had the problems on time management, insufficient knowledge on civics content, unclear information illustrating in materials and behavior evaluations.2)Teachers and students perceived that the students had the 23 characteristics based on 5 focus points at the high levels.3)The problem solutions for teaching civics courses were integrating of civics courses with others courses or with fundamental social studies courses; setting the division responsible for teacher training workshops, organizing community service activities; emphasizing on behavior modification; using learning resources online and local learning materials and authentic assessment.